Antioxidant and tyrosinase inhibitory activity of Rosa roxburghii fruit and identification of main bioactive phytochemicals by UPLC‐Triple‐TOF/MS. (15th February 2017) - Zeng, Fangfang; Ge, Zhiwei; Limwachiranon, Jarukitt; Li, Li; Feng, Simin; Wang, Yansheng; Luo, Zisheng
Summary: The content of bioactive phytochemicals, antioxidant activity and tyrosinase inhibitory activity of the hydroalcoholic extracts of Rosa roxburghii were determined. Yellow fruits of cultivated R. roxburghii showed the highest phenolic content (154.81 mg gallic acid g −1 ), and the green fruits of wild R. roxburghii showed higher content of flavonoid and triterpenoid. Rosa roxburghii fruits from different cultivars and maturity stages all demonstrated as good antioxidant agents and tyrosinase inhibitors, with IC50 value about twice of the positive standard in the DPPH assay and triple of the standard in the tyrosinase inhibitory activity assay. Nineteen compounds, mainly ellagic acids and its derivatives, flavonoids and their glycosides were identified by UPLC‐Triple‐TOF/MS analysis. As the first study of bioactive phytochemicals of R. roxburghii by UPLC‐MS, the present research may provide valuable information for fulfilling the potential of R. roxburghii in the functional food area. Abstract : Antioxidant and tyrosinase inhibitory activity of Rosa roxburghii fruit and identification of main bioactive phytochemicals by UPLC‐Triple‐TOF/MS.